Research on the identification of high-resistance ground faults in the flexible DC distribution network based on VMD–inception–CNN - Zheng, Feng; Peng, Yaling; Jiang, Changxu; Lin, Yanzhen; Liang, Ning (Frontiers in Energy Research, 2023)
With the rapid development of flexible DC distribution network, fault detection and identification have also attracted people 's attention. High resistance grounding fault poses a great challenge to the distribution network. The fault current is very small and random, which makes it difficult to detect and identify. The traditional overcurrent protection device cannot identify and act. This paper proposes a fault detection method based on variational mode decomposition ( VMD ) combined with convolutional neural network ( CNN ) of Inception module. This method firstly uses VMD to decompose the positive transient voltage. Secondly, it inputs the decomposed signal into CNN network for training to obtain the optimal parameters of the model. Finally, the model performance is tested based on PSCAD / EMTDC simulation platform. Experiments show that the detection method is accurate and effective. It can realize the accurate identification of seven different fault types.